Urgensi Literasi Digital dalam Membangun Ekosistem Pendidikan Modern: Studi Literatur Review - Rafizah; Nayla Khairani; Zalikha Syahajir Silitonga; Dina Ampera; Halimul Bahri (CAHAYA: Journal of Research on Science Education, 2026)
The rapid advancement of digital technology has transformed educational systems worldwide, making digital literacy an indispensable competency for students, teachers, and educational stakeholders. This study aims to examine the urgency of digital literacy in developing a modern educational ecosystem and to identify its contributions to improving educational quality in the digital era. A Systematic Literature Review (SLR) approach was employed to synthesize and analyze relevant scholarly publications indexed in reputable databases. The review process involved article identification, screening, eligibility assessment, and thematic analysis of studies published within the last decade. The findings reveal that digital literacy plays a pivotal role in enhancing critical thinking, problem-solving, creativity, communication, and collaboration skills, which are essential competencies for the twenty-first century. Furthermore, digital literacy supports the effective integration of technology into teaching and learning processes, promotes lifelong learning, and strengthens digital citizenship among learners. However, challenges such as unequal access to technology, limited digital competence among educators, and inadequate institutional support remain significant barriers. Therefore, the integration of digital literacy into educational curricula and policies is no longer optional but imperative. Sustainable collaboration among policymakers, educational institutions, teachers, and communities is required to establish an inclusive, adaptive, and resilient digital education ecosystem capable of meeting future educational demands.